Chinese Herbal Medicine for Wilson's Disease: A Systematic Review and Meta-Analysis - Xu, Meng-Bei; Rong, Pei-Qing; Jin, Ting-Yu; Zhang, Pei-Pei; Liang, Hai-Yong; Zheng, Guo-Qing (Frontiers in Pharmacology, 2019)
Wilson’s disease (WD) is a rare autosomal recessive inherited disorder of chronic copper toxicosis. Currently, Chinese herbal medicines (CHM) is widely used for WD. Here, we conducted an updated systematic review to investigate the efficacy and safety of CHM for WD and its possible mechanisms. Randomized-controlled clinical trials (RCTs), which compared CHM with Western conventional medicine or placebo for WD, were searched in six databases from inception to July 2017. The methodological quality was assessed using 7-item criteria from the Cochrane’s collaboration tool. All the data were analyzed using Rev-Man 5.3 software. Eighteen studies involving 1,220 patients were identified for the final analyses. Score of study quality ranged from 2/7 to 4/7 points. Meta-analyses showed that CHM could significantly increase 24-h urinary copper excretion, and improve liver function and the total clinical efficacy rate for WD compared with control (p<0.05). Additionally, CHM was well tolerated in patients with WD. The underlying mechanisms of CHM for WD are associated with reversing the ATP7B mutants, exerting anti-oxidation, anti-inflammation and anti-hepatic fibrosis effects. In conclusion, despite the apparent positive results, the present evidence supports, to a limited extent because of the methodological flaws and CHM heterogeneity, that CHM paratherapy can be used for patients with WD but could not be recommended as monotherapy in WD. Further rigorous RCTs focusing on individual CHM formula for WD are warranted.